John Wright Hunt: The Interesting Life Of a North Carolina Native - Houser, Jeffrey (Lulu Press inc., 2016)
It all started with a slip of paper… Many of those interested in genealogy can attest to getting started on a simple research endeavor but ended up becoming a very involved project. What may have begun as looking for a few newspaper articles soon turned into something that required a great deal of research and an equal amount of time being consumed to find answers about the life of a person. So is the case with this biography of John W. Hunt. In the year 2015, I was serving on the Board of Directors for the Olde Mecklenburg Genealogical Society in Charlotte, North Carolina. At the conclusion of our monthly meeting in August, a colleague also serving on the Board, , Dr. Ted Lucas, Jr., got my attention and literally slid a piece of paper with a name scratched on it across the table to me and asked if I could “just see what I might be able to find out about him,” the ‘him’ being John W. Hunt. Ted had been doing his own family genealogy research for many, many years and this particular member of his family, often referred to as “Uncle John”, had become a bit of an enigma when he tried to locate definitive information about Hunt. Ted knew that I was regularly engaged in historical and genealogical research around the Charlotte area and felt that maybe I could come across something that he hadn’t stumbled upon yet. My initial research took place over the course of six weeks, after which I was able to present Ted with a booklet consisting of about fifteen pages that mainly contained newspaper articles and some other details I was able to find using online resources about Hunt. Ted was very appreciative of my efforts and he looked through the report with great interest after I had handed it to him. However, something about John Hunt kept tugging at me. I had found some very intriguing aspects of his life and, because I am naturally inquisitive, I wanted to know more. What started out with a slip of paper grew into a full-blown research project that strung itself out for more than seven months. It seemed that almost every time I discovered something else about John Hunt’s story, it led to new pieces of information or required more in-depth research about certain topics. A myriad of phone calls, letters and e-mails were sent to numerous organizations to request information about Hunt that they may have been holding in their archives. This biography is a culmination of that research. While several aspects of Hunt’s life were very hard to ascertain, his general life story is captivating and is likely to keep the reader of this work looking forward to turning to the next page to find out “what John did next”. It is my hope that his story will be of interest to the cities and families that he was connected to and that they may hold this work in their historic files for future generations to refer to and be able to become familiar with the interesting life of John W. Hunt.
Houser, Jeffrey J. John Wright Hunt: The Interesting Life Of a North Carolina Native. Raleigh, Lulu Press inc., 2016. Includes: John W. Hunt Presentation, December 2016. https://youtu.be/9tGJeDrUxr0
Keywords: North Carolina--History; Georgia--History; Turpentine